Sciadonic acid attenuates high-fat diet-induced bone metabolism disorders in mice - Yao, Shiwei; Lu, Hongling; Zhou, Tianhuan; Jiang, Qihong; Jiang, Chenkai; Hu, Wenjun; Li, Mingqian; Tan, Chin Ping; Feng, Yongcai; Du, Qun; Shen, Guoxin; Xiang, Xingwei; et al. (Royal Society of Chemistry, 2024)
High-fat diet (HFD) has been associated with certain negative bone-related outcomes, such as bone metabolism disruption and bone loss. Sciadonic acid (SC), one of the main nutritional and functional components of Torreya grandis seed oil, is a unique Δ5-unsaturated-polymethylene-interrupted fatty acid (Δ5-UPIFA) that has been claimed to counteract such disorders owing to some of its physiological effects. However, the role of SC in ameliorating bone metabolism disorders due to HFD remains unclear. In the present investigation, we observed that SC modulates the OPG/RANKL/RANK signaling pathway by modifying the lipid metabolic state and decreasing inflammation in mice. In turn, it could balance bone resorption and formation as well as calcium and phosphorus levels, enhance bone strength and bone mineral density (BMD), and improve its microstructure. In addition, SC could inhibit fat vacuoles in bone, reverse the phenomenon of reduced numbers and poor continuity of bone trabeculae, and promote orderly arrangement of collagen fibers and cartilage repair. This study provides some theoretical basis for SC as a dietary intervention agent to enhance bone nutrition. © 2024 The Royal Society of Chemistry.